Study Of Cytotoxic Mechanism And The Role Of Microrna In Mda-Mb-231 Cell Lines Treated With Phaleria Macrocarpa (Boerl.) Fruit Ethyl Acetate Fraction (Pmeaf) - Nowroji, Kavitha (2017)
Phaleria macrocarpa is a well-known medicinal plant which exhibited cytotoxicity against various cancerous cells. The objective of this study was to determine the in vitro cytotoxicity effect by biochemical assay through the regulation of miRNAs on MDA-MB-231 treated with Phaleria macrocarpa ethyl acetate fraction (PMEAF). Total phenolic content of PMEAF was expressed as 14.91 ± 0.97 mg GAE/g. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and CyQuant Cell Proliferation assay results indicated that PMEAF is a potential anticancer agent with the average IC50 values of 18.10 μg/mL.